Coalescence Phenomenon in the Three Photon Quantum Interferences. Issue 1 (March 2021) - Ripala, D P; Rohedi, A Y; Suryadi
Abstract: We present the theoretical study of three-photon interference in the six ports Mach-Zehnder Interferometer (6p-MZI). The 6p-MZI consist of two lossless symmetrically balanced tritters and three independently controllable phase modulators inserted in each photon line path between the tritters. Three photons (Fock state) are injected onto the first tritter input ports and measured in second tritter output ports. By independently varying the phases states of the three photons, one can control the detection probability of photon numbers at final tritter output ports. The calculation results demonstrated that, at the specific combination of phase states, the three photons interference exhibited a coalescence phenomenon, which is the three-photons detected at the same output port. Interestingly, the probability of detecting photons in all combination modes of |0, 0, 3), |0, 3, 0〉, and |3, 0, 0〉 are monotonously in the equal values.